Cooperation Networks: Competitive Motivators in Training, Facilitators and Hinders of Interorganizational Relationships - Antunes do Nascimento, Esdras (2023)
Based on the cooperation networks approach, this article analyzes how small and medium biscuit producing and trading companies in the Southwest region of Bahia seek new learning, competitiveness and business opportunities. The study evaluates and characterizes the competitive factors that have motivated the formation of the cooperation network and stimulated the establishment of inter-organizational bonds, describing the facilitators and obstacles to relationships. The results found allow us to conclude that the market competitive motivators are related to the search for representativeness, credibility and complementarity, aiming at visibility and prospecting for new business. In addition, the decision to enter into interorganizational relationships has been facilitated by associations, local culture and participation of local development agents, with prominence for the participation of Sebrae (BA), finding, however, difficulties in strengthening trust in social relations and in the commitment of actors in joint actions.